Synthesis and characterization of biphenyldicarboxylic acid-modified poly(1, 4-cyclohexylenedimethylene terephthalate) copolyesters. Issue 2 (11th April 2022) - Song, Tao; Wang, Qingyin; Li, Jianguo; Chen, Xuejun; Liu, Shaoying; Wang, Gongying
Abstract: A new copolyesters of poly(1, 4-cyclohexylenedimethylene terephthalate-co-4, 4'-biphenydicarboxylate) (PCTB) with different compositions were synthesized from terephthalic acid, 1, 4-cyclohexanedimethanol and 4, 4'-biphenyldicarboxylic acid (BDA) via esterification-polycondensation reaction. The synthesized copolyesters were analyzed by 1 H-NMR, 13 C-NMR, FT-IR, GPC, intrinsic viscosity, DSC, TGA and tensile testing, respectively. The 1 H-NMR, 13 C-NMR and FT-IR results verify the successful introduction of BDA into poly(1, 4-cyclohexylenedimethylene terephthalate (PCT) chains. The introduction of BDA into PCT chains can effectively lower the melting point of PCT, making it easier to process. The glass transition temperature of PCTB is higher than 103 °C and its thermal stability is better than that of PCT. The rheological tests confirm the enhanced melting stability of PCT after introducing BDA into PCT chains. Furthermore, the PCTB, which owns the comparable mechanical properties to PCT, is a tough polymer with the higher Young's modulus (above 230 MPa), the higher tensile strength (above 41 MPa) and the higher elongation at break (above 159%). Graphical Abstract: UF0001